Deep Brain Stimulation of Caudal Zona Incerta and Subthalamic Nucleus in Patients with Parkinson's Disease: Effects on Diadochokinetic Rate - Fredrik Karlsson; Elin Unger; Sofia Wahlgren; Patric Blomstedt; Jan Linder; Erik Nordh; Hamayun Zafar; Jan van Doorn (Parkinson's Disease)
The hypokinetic dysarthria observed in Parkinson's disease (PD) affects the range, speed, and accuracy of articulatory gestures in patients, reducing the perceived quality of speech acoustic output in continuous speech. Deep brain stimulation (DBS) of the subthalamic nucleus (STN-DBS) and of the caudal zona incerta (cZi-DBS) are current surgical treatment options for PD. This study aimed at investigating the outcome of STN-DBS (7 patients) and cZi-DBS (7 patients) in two articulatory diadochokinesis tasks (AMR and SMR) using measurements of articulation rate and quality of the plosive consonants (using the percent measurable VOT metric). The results indicate that patients receiving STN-DBS increased in articulation rate in the Stim-ON condition in the AMR task only, with no effect on production quality. Patients receiving cZi-DBS decreased in articulation rate in the Stim-ON condition and further showed a reduction in production quality. The data therefore suggest that cZi-DBS is more detrimental for extended articulatory movements than STN-DBS.